The Ruthless Wealth of Health: Power Dynamics of Hospital Industry in Sulu Province - Ballesteros, Jenneth (JPAIR Multidisciplinary Research, 2022)
The people in Sulu usually go to hospitals and seek medical treatment when they are already in a severe condition that doctors can no longer cure and help. The qualitative method using focus group discussion and workshop conduct was employed, and the most appropriate sampling design is purposive. Four participants were invited and represented the actors from the regularity agent, supply side, demand side, and alternative substitute. Sixteen participants purposively drew and shared their opinions in the workshop. Findings show that the actors involved in the regulatory framework created by Republic Act of the Philippines and the policies and regulations were all done at the national level; the hospital director, administration, health provider, external suppliers together with the hospital and medical facilities, equipment, buildings, and services comprised the supply side in the hospital industry; the markets of the health services were the entire citizen of Sulu; alternative substitute like the traditional medicines and procedures like hilot were accepted by the Tausug. Lastly, all the interactions displayed by the different actors coming from the regulatory agent, supply side, demand side, and the alternative substitute described the nature and performance of the hospital industry in Sulu. Nonetheless, producing a climate of quality health care service.
Keywords: Health Science; hospital industry in Sulu province; qualitative method; purposive sampling design; Jolo; Sulu; Province; Philippines